Research progress on toughening polylactic acid by renewable and biodegradable polymers - Wei, Ze-chang; Cai, Chen-yang; Wang, Xing; Fu, Yu (Cai liao gong cheng = Journal of materials engineering, 2019)
Polylactic acid (PLA), a new type of bio-based renewable biodegradable material, has attracted more and more attention because of its advantages with high mechanical strength, ease of processing, high melting point, biodegradability and biocompatibility. However, its inherent brittl-eness, low elongation at break and breaking strength severely limit its practical application and has also led to more extensive and comprehensive research. This review summarizes the research progress of toughening polylactic acid with biodegradable macromolecules, especially focusing on the updated development on bio-based polyesters, bio-based elastomers, plant-based biopolymers, natural rubber and vegetable oils, and biomacromolecules, and meanwhile, the problem of weak impact toughness and low crystallization rate and low thermal transition temperature of polylactic acid after improving toughness was proposed, and the future direction of development and the subjects needed to focused on was finally predicted.